2011
DOI: 10.1016/j.biortech.2010.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing solubilisation and methane production kinetic of switchgrass by microwave pretreatment

Abstract: This study investigated the effects of microwave pretreatment of switchgrass in order to enhance its anaerobic digestibility. Response surface analysis was applied to screen the effects of temperature and time of microwave pretreatment on matter solubilisation. The composite design showed that only temperature had a significant effect on solubilisation level. Then the effects of the microwave pretreatment were correlated to the pretreatment temperature. The sCOD/tCOD ratio was equal to 9.4% at 90°C and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 24 publications
(22 reference statements)
4
27
1
Order By: Relevance
“…In our study, the solubilization of both the leaf and stem switchgrass fractions were significantly affected by the microwave final temperature (P<0.0001), holding time (leaf: P=0.0111; stem: P=0.0002), and heating rate (leaf: P=0.0010; stem: P=0.0002). However, the exposure time had a smaller influence on the solubilization (sCOD/tCOD) of whole fresh plants for switchgrass (Jackowiak et al 2011b). Interestingly enough, a study on whole wheat straw showed that the solubilization (sCOD/tCOD) increased with longer holding times at the target temperature (Jackowiak et al 2011a).…”
Section: Solubilization Of Switchgrass Leaf and Stem Fractionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the solubilization of both the leaf and stem switchgrass fractions were significantly affected by the microwave final temperature (P<0.0001), holding time (leaf: P=0.0111; stem: P=0.0002), and heating rate (leaf: P=0.0010; stem: P=0.0002). However, the exposure time had a smaller influence on the solubilization (sCOD/tCOD) of whole fresh plants for switchgrass (Jackowiak et al 2011b). Interestingly enough, a study on whole wheat straw showed that the solubilization (sCOD/tCOD) increased with longer holding times at the target temperature (Jackowiak et al 2011a).…”
Section: Solubilization Of Switchgrass Leaf and Stem Fractionsmentioning
confidence: 99%
“…The sVS/VS increase ranged from 1.5% to 154.0% in the leaf fraction, and from 2.1% to 130.3% in the stem fraction (Table 3), depending on the microwave final temperature, holding time, and heating rate. Jackowiak et al (2011b) also reported that microwave pretreatment improved the solubilization of switchgrass, but whole plants were used in that study. In our study, the solubilization of both the leaf and stem switchgrass fractions were significantly affected by the microwave final temperature (P<0.0001), holding time (leaf: P=0.0111; stem: P=0.0002), and heating rate (leaf: P=0.0010; stem: P=0.0002).…”
Section: Solubilization Of Switchgrass Leaf and Stem Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave energy has been recently explored as a potential technology to enhance the pretreatment of various lignocellulosic materials for the production of biofuels (Eskicioglu et al, 2007a,b;Taherzadeh and Karimi, 2008;Alvira et al, 2010;Shi et al, 2011;Jackowiak et al, 2011). It has more rarely been applied to the specific extraction of lignin, either as a pretreatment technique prior to enzymatic mild acidolysis (Zoia et al, 2008)o ri n combination with ionic liquids (Tan et al, 2009;Sun et al, 2009;Fu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline pretreatment is believed to cause swelling of the lignocellulosic structure, leading to an increase in internal surface area, separation of structural linkage between lignin and carbohydrates, and the disruption of lignin structure (Ong et al 2010;Kashaninejad and Tabil 2011). As described in the literature, microwave treatment produces a rapid volumetric heating throughout the material, resulting in alteration of physio-chemical characteristics of the material, which enables and accelerates the breaking down of the lignin-hemicellulose complex and increases the exposure of cellulose surface to cellulase (Ma et al 2009;Jackowiak et al 2011). In addition, Gabhane et al (2011) reported that microwave treatment has better efficacy (more than 10% improvement in sugar yield) on garden biomass than autoclave and hot plate treatment techniques.…”
Section: Resultsmentioning
confidence: 99%